EXPLORING GENERIC STRUCTURE POTENTIAL OF SELECTED EDITORIALS IN THE MYANMAR TIMES NEWSPAPER - Ae Mon Kyaw; Xin Zhiying (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2019)
Systemic Functional Linguists introduced Generic Structural Potential (GSP) that can be used to distinguish different social activities of a text. A variety of researches have been conducted on Generic Structural Potential of the editorials of other countries. However, no research has been conducted about the editorials of Myanmar newspaper. Therefore, The Myanmar Times newspaper, written in English, is chosen to carry out a research. The aim of the research paper is to identify the schematic structural elements of the editorials in The Myanmar Times newspaper. The materials are measured using Generic Structure Potential proposed by Halliday and Hason (1985). The result of the study shows that there are two obligatory elements and five optional elements. Heading (H), and Contributing the Writer’s Opinion (O) are obligatory while Picture (P), Caption(C ), Addressing the issue (AI) , Background Information (BI), and Discussing the issue Raised (D) are optional elements. The sequence of the elements follows the procedure H^ (P)^{ *(BI) *(AI) *(D) }^O.